2022
DOI: 10.1039/d2py01180h
|View full text |Cite
|
Sign up to set email alerts
|

Using precision polymer chemistry for plastics traceability and governance

Abstract: Resolving the anonymity of plastic materials is critical for safeguarding the well-being of our natural environments and human health. Herein, we explore how contemporary polymer chemistry – in the form...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In this way, materials can be continuously tracked and what happened to the material beforehand can always be clearly looked up across research groups, companies, countries, and production sites. This will eventually also make recycling more accessible, [ 222 ] as one immediately knows what is in the material and how it can be reused. In this way, digital processes can make materials greener and more sustainable as well as material flows can be closed.…”
Section: Future Trends and Challengesmentioning
confidence: 99%
“…In this way, materials can be continuously tracked and what happened to the material beforehand can always be clearly looked up across research groups, companies, countries, and production sites. This will eventually also make recycling more accessible, [ 222 ] as one immediately knows what is in the material and how it can be reused. In this way, digital processes can make materials greener and more sustainable as well as material flows can be closed.…”
Section: Future Trends and Challengesmentioning
confidence: 99%
“…A "new plastics economy", which has among its key elements the expansion and improvement of the non-biodegradable plastic recycling processes, has been promoted [5]. In this context, many researchers from both academia and industry have devoted their studies to new strategies leading to the improvement of collection, sorting and recycling technologies [6]. To improve both the cheapness and speed of plastic mechanical recycling processes, automated sorting systems based on the intrinsic chemicophysical properties of polymers have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Sequence-defined macromolecules have shown promise for applications in data storage, cryptography, biomedical or pharmaceutical applications, as well as catalysis. [6][7][8][9] Current applications focus on properties obtained through physical bond formation, such as supramolecular interactions like host-guest chemistry and self-assembly or dynamic covalent bonds, often in an attempt to mimic natural polymers. [5,10] Studies have shown that macromolecularly-defined oligomers or polymers present a promising avenue for investigating the effect of macromolecular structure (for example chain length or monomer positioning) on physical, thermal, and optical properties of bulk materials.…”
mentioning
confidence: 99%